Welcome to Our Class! Building Classroom Rapport to Support the Development of Social and Emotional Learning Skills. (April 2023) - Michael, Elizabeth; Bailey, Pamela; Benner, Gregory J.; Sanders, Sara
In this article, we describe practical, usable ways teachers can build rapport with students, particularly students with and at risk for emotional and behavioral disorders. By establishing rapport, teachers can increase the effectiveness of the social and emotional learning curriculum and interventions delivered. Specifically, the warm welcomes, transitions, emotion checks, two by 10, and optimistic closures strategies are described.